"You Need to Stop Talking About This!": Verbal Rumination and the Costs of Social Support. (18th June 2013) - Afifi, Tamara; Afifi, Walid; Merrill, Anne F.; Denes, Amanda; Davis, Sharde
<x xml:space="preserve">Abstract</x> This study examined whether the type of support individuals receive when they are verbally ruminating affects their cognitive rumination (brooding), anxiety, and relationship satisfaction; 233 young adults were randomly assigned to be the subject, 233 others the confederate. The confederate was trained to provide "good support" or "poor support" to the subject who talked about a topic he/she had been verbally ruminating about recently. When individuals verbally ruminated and received poor support, they became more anxious and dissatisfied with the friendship. When individuals received good support, they were more satisfied with their friendship, but their anxiety was not significantly reduced. In addition, verbal rumination was directly associated with more brooding after the conversation, regardless of the type of support provided.